Biodiversity of plants of the Talgar, Enbekshikazakh districts of the Almaty region (Experimental biology, 2019)
One of the global challenges of our time is to study the problems and preserve the biological diversity of plants. Therefore, the study of plant biodiversity in any region will always be relevant.This article presents the results of a study obtained in the course of conducting a systematic analysis of the flora of Talgar and Enbekshikazakh regions the Almaty region. It was revealed that the flora of the study area includes 114 families, of which 10 leading families make up 60.48% of the total species composition of the flora of the study area. The following families occupy the leading position in this taxonomic composition: Asteraceae (225 species, or 14.60%, 71 genus), Poaceae (132 species or 8.56%), Fabaceae - (115 species or 7.46%). The largest genera are Astragalus (44 species or 7.94%), Allium (28 species or 5.05%), Carex (27 species, 4.87%), Potentilla (23 species or 4.15%).The flora was studied with using traditional methods of floristic and geobotanical research, the main of which was route reconnaissance method.Based on the analysis of literature data, viewing of the herbarium fund of the Institute of Botany and Phytoinduction of the National Academy of Sciences of Kazakhstan, as well as their own research on the study and collection of plants in the Almaty region, a preliminary annotated list of flora was compiled, including 1541 species belonging to 554 genera and 114 families.Key words: flora, Talgar, Enbekshikazakh distric  ts Almaty region, systematic analysis, biodiversity of  plants.